Modul konsep Pembelajaran Berbasis Alam Perspektif Al-Qurân - Budi Santoso (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The purpose of this study is to reveal epistemologically the concept of nature-based learning in the perspective of the Qur'an and prove the concept of nature-based learning perspective of the Qur'an as one of the effective efforts in improving the quality of Education. This study uses primary sources in the form of verses of the Qur'an and several books of tafsir as well as scientific works related to research. The Data obtained were then analyzed using qualitative methods and maudhi'i Tafseer methods that serve to find an explanation of the verses related to nature-based learning in a comprehensive manner. The results of this study concluded that the concept of nature-based learning is an effort by educators to learners in developing knowledge competence (al-Baqarah/2:30-33), attitude (al-Hujurât/49:13), and skills (al-Alaq/96:1-5) by utilizing the natural environment as a tool, material, media, and a place of learning that aims to serve Allah SWT (al-Dzâriyat/51:56) and perform 30, shâd/38:26) that preserve and prosper the Earth. The implication of the results of this study is the improvement of spiritual and social attitudes of learners because all learning activities are associated with aspects of the divine.